Synthesis of a New Phorbazole and Its Derivatives - Muderawan, I Wayan; Loughlin, Wendy A.; Young, David J. (Synthesis, 2021)
Phorbazoles are chlorinated marine alkaloids containing pyrrole, oxazole and phenol ring units, and differ in the number and positions of chlorine atoms. They are isolated from sea sponges and nudibranchs. In this work, a convenient synthetic method leading to a new phorbazole and its derivatives is developed. This synthesis of synthetic phorbazole G and its derivatives is achieved in seven steps in good overall yields of 26–52%. It involves formation of the pyrrole-oxazole skeleton followed by chlorination. The pyrrole-oxazole skeleton is synthesized from pyrrole and substituted acetophenones, and the key step involves cyclodehydration of amide intermediates to give protected oxazoles, followed by hydrolysis.
Keywords: phorbazoles; oxazoles; pyrroles; chlorination; natural products